The wish to die among palliative home care clients in Ontario, Canada: A cross-sectional study. Issue 1 (December 2016) - Freeman, Shannon; Smith, Trevor; Neufeld, Eva; Fisher, Kathy; Ebihara, Satoru
Abstract Background In the pursuit to provide the highest quality of person centered palliative care, client preferences, needs, and wishes surrounding end of life should be used to inform the plan of care. During a clinical assessment for care services, clients may voluntarily express a 'wish to die' either directly to the clinician or it may be indirectly reported second-hand to the clinician through an informal caregiver or family member. This is the first study using data gathered from the interRAI Palliative Care Assessment instrument (interRAI PC) to examine socio-demographic, clinical, and psycho-social factors of palliative home care clients with the voluntary expression of a 'wish to die now'. Factors associated with the risk for depression within this group were also identified. Awareness and understanding of clients who express the 'wish to die' is needed to better tailor a person-centered approach to end-of-life care. Methods This cross-sectional study included assessment records gathered from 4, 840 palliative home care clients collected as part of pilot implementation of the interRAI PC assessment instrument in Ontario, Canada from 2006 through 2011. Results During the clinical assessment, 308 palliative home care clients (6.7 %) had voluntarily expressed a 'wish to die now'. Independent factors emerging from multivariate logistic regression analyses predicting the expression of a 'wish to die' included not being married/widowed, a shorter estimated prognosis, depressive symptoms, functional impairment, too much sleep (excessive amount), feeling completion regarding financial/legal matters, and struggling with the meaning of life. Among persons who expressed a 'wish to die now', those who exhibited depressive symptoms (23.8 %, n = 64) were also more likely to exhibit cognitive impairment, have decline in cognition in the last 90 days, exhibit weight loss, have informal caregivers exhibiting distress, 'not have a consistent positive outlook on life' and report 'struggling with the meaning of life'. Conclusion When clients voluntary express a wish to die clinicians should take notice and initiate follow-up to better understand the context of this meaning for the individual. Clients who expressed a 'wish to die' did not all experience pain, depression, and psychological distress suggesting an individualized approach to care management be taken.